C-7 modified flavonoids as novel tyrosyl-tRNA synthetase inhibitors. Issue 11 (18th January 2017) - Xiao, Zhu-Ping; Wei, Wei; Liu, Qi; Wang, Peng-Fei; Luo, Xing; Chen, Fang-Yuan; Cao, Yang; Huang, Hong-Xia; Liu, Mi-Mi; Zhu, Hai-Liang
Abstract : Twenty C-7 modified flavonoids were designed and synthesized. Abstract : Twenty C-7 modified flavonoids were designed and synthesized. Biological evaluation in vitro indicated that compounds generated by SYBYL-X with high scores also showed good inhibitory activities against TyrRS. Compounds containing the nargenin core exhibit better enzyme inhibitory activities than other flavonoid cores, with ( S )-5-hydroxy-4′-hydroxy-7-(2-morpholino-2-oxoethoxy)-2, 3-dihydroflavone (b1 ) being the most active (IC50 = 0.10 ± 0.01 μM) in all assayed compounds. All compounds were also assayed for antimicrobial activities against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa, andb1 also displayed excellent activity, showing 6-fold more potent than the marketed antibiotic ciprofloxacin. In comparison with Gram-positive organism, all these derivatives exhibited better activity against Gram-negative organism, and did not displayed significant differences between the two assayed Gram-negative strains ( E. coli ATCC 8739 and P. aeruginosa ATCC 9027).